Biophysical Evaluation of Rhesus Macaque Fc Gamma Receptors Reveals Similar IgG Fc Glycoform Preferences to Human Receptors - Crowley, Andrew R.; Osei-Owusu, Nana Yaw; Dekkers, Gillian; Gao, Wenda; Wuhrer, Manfred; Magnani, Diogo M.; Reimann, Keith A.; Pincus, Seth H.; Vidarsson, Gestur; Ackerman, Margaret E. (Frontiers in Immunology, 2021)
Rhesus macaques are a common non-human primate model used in the evaluation of human monoclonal antibodies, molecules whose effector functions depend on a conserved N-linked glycan in the Fc region. This carbohydrate is a target of glycoengineering efforts aimed at altering antibody effector function by modulating the affinity of Fcγ receptors. For example, a reduction in the overall core fucose content is one such strategy that can increase antibody-mediated cellular cytotoxicity by increasing Fc-FcγRIIIa affinity. While the position of the Fc glycan is conserved in macaques, differences in the frequency of glycoforms and the use of an alternate monosaccharide in sialylated glycan species add a degree of uncertainty to the testing of glycoengineered human antibodies in rhesus macaques. Using a panel of 16 human IgG1 glycovariants, we measured the affinities of macaque FcγRs for differing glycoforms via surface plasmon resonance. Our results suggest that macaques are a tractable species in which to test the effects of antibody glycoengineering.